2004
DOI: 10.2746/0425164044868459
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the medial palmar intercarpal ligament in the Thoroughbred: technique and normal appearance

Abstract: Summary Reasons for performing study: Tearing of the medial palmar intercarpal ligament (MPICL) has been recognised as a cause of lameness in the Thoroughbred, but diagnosis is difficult due to the nonspecific clinical signs, and can be achieved only by performing arthroscopy on the mid carpal joint (MCJ). It would be beneficial to be able to image the MPICL using ultrasonography to determine whether pathology is present in the ligament in order to aid diagnosis and prognosis. Objectives: To determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…To our knowledge, this is one of the first studies describing CT arthroscopic anatomy and characteristics of intercarpal ligaments in horses. Previously, traditional imaging modalities have not been successful at visualizing entire ligamentous structures . Results of this study indicate that the entire medial palmar intercarpal ligament, lateral palmar intercarpal ligament as well as the radiocarpal ligament, transverse intercarpal ligaments, and palmar carpal ligament were easily identifiable by this method.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…To our knowledge, this is one of the first studies describing CT arthroscopic anatomy and characteristics of intercarpal ligaments in horses. Previously, traditional imaging modalities have not been successful at visualizing entire ligamentous structures . Results of this study indicate that the entire medial palmar intercarpal ligament, lateral palmar intercarpal ligament as well as the radiocarpal ligament, transverse intercarpal ligaments, and palmar carpal ligament were easily identifiable by this method.…”
Section: Discussionmentioning
confidence: 74%
“…Antemortem diagnosis of intercarpal ligament pathology remains difficult due to the lack of specific clinical signs complexity of the carpal anatomy and limitations with routine diagnostic imaging modalities. Radiography and ultrasound have a low sensitivity for the identification or diagnosis of pathology of medial palmar intercarpal ligament and lateral palmar intercarpal ligament . Radiographic signs are limited to abnormalities at the ligament entheses and variation exists in the carpal bone margins that may or may not be associated with ligament damage .…”
Section: Introductionmentioning
confidence: 99%
“…In the carpus, the intra-articular ligaments and most of the articular surfaces cannot be imaged. The technique can, however, be used to evaluate soft tissues associated with the joint, including the collateral ligaments, joint capsule, other associated ligaments, and the menisci (11). In the present study, joint effusion was demonstrated in cases of arthritis.…”
Section: Resultsmentioning
confidence: 57%
“…The normal ultrasonographic appearance of the palmar intercarpal ligaments has been described (Driver et al . ), but lesions diagnosed by ultrasonography have not been documented. These ligaments can be visualised by MRI (Nagy and Dyson ) and computed tomography (Gray et al .…”
mentioning
confidence: 99%